Mathematics of Program Construction 11th International Conference, MPC 2012, Madrid, Spain, June 25-27, 2012, Proceedings - Gibbons, Jeremy; Nogueira, Pablo (Theoretical Computer Science and General Issues, 2012)
This book constitutes the refereed proceedings of the 11th International Conference on Mathematics of Program Construction, MPC 2012, held in Madrid, Spain, in June 2012. The 13 revised full papers presented together with three invited talks were carefully reviewed and selected from 27 submissions. The papers are organized in topical sections on security and information flow, synchronous and real-time systems, algorithms and games, program calculi, tool support, algebras and datatypes, and categorical functional programming.